Myocarditis following mRNA COVID‐19 vaccination: call for endomyocardial biopsy - Daniel Kiblboeck; Karin Klingel; Martin Genger; Selina Traxler; Nathalie Braunsteiner; Clemens Steinwender; Joerg Kellermair (ESC Heart Failure)
Abstract Acute myocarditis following mRNA COVID‐19 vaccination was reported by the European Medicine Agency safety committee as a rare adverse event. We present a case series of three young male patients with suspected acute myocarditis following BNT162b2 mRNA COVID‐19 vaccination including results of endomyocardial biopsies (EMB). Additionally, we analysed EMB of another 21 patients with clinically suspected acute myocarditis following vaccination to determine the pathohistological pattern. Overall, EMB revealed acute lymphocytic myocarditis in 5 (20.8%), chronic lymphocytic myocarditis in 6 (25%), cardiac sarcoidosis in 1 (4.2%), healed myocarditis in 6 (25%), and other diagnoses with cardiac damage of unclear aetiology in 6 (25%) cases. Our findings support the necessity of EMB in patients with suspected acute myocarditis following mRNA COVID‐19 vaccination presenting with reduced EF to establish a correct and definite diagnosis. Concerns of these rare severe adverse events after COVID‐19 immunization should not undermine its value for the global community.